(3OQhS eaUdI hJeGQjf eMdhdIs - (3CMSf(B, (3WjGQs ((3GdLRGFQ(B:s (3OGQ gheI(B,s, 2019)
(3eONd dYde GdGMUGA, fHPI JGQjNjI Yf Yde GdGMUGA heLGdGJ GSJNOGe GdGMUGA aj GdGbJUGO hGdJSjjQ, hYQV GdHjGfGJ, HGdGVGaI Gdi ebGjjS GdfRYI GdeQcRjI, HeG ajg GdhSW GdMSGHj eY GdhSjW hGdefhGd, hGdYdGbI Hjfge, HGdGVGaI Gdi ebGjjS GdJTJJ hGdTcd, h aj GdCNjQ PcQ dfG NUGFU GdJhRjYGJ GdGMUGFjI deJZjQjf,eY GdGfMOGQ hGdGQJHGW GdNWj, HGdGVGaI Gdi GdSdGSd GdRefjI, hNJe dfG HGdCQbGe GdbjGSjI(B.s
(3eQGLY U(B.311s
Keywords: (3GdGMUGA GdhUajs